Institutional governance and degraded agricultural land management in supporting regional food security - Prantama, Muhammad Barqah; Wijaya, Andy Fefta; Rozuli, Ahmad Imron; Hakim, Muhammad Lukman (Journal of Degraded and Mining Lands Management, 2026)
?Agricultural land degradation and land conversion increasingly threaten regional food security in Malang Regency, East Java. This study examined how biophysical vulnerability—particularly soil organic carbon decline in Inceptisol-dominated systems—interacted with land governance and agricultural productivity. This study adopted a qualitative case study approach, supported by secondary data on land use, soil characteristics, harvested area, and rice production, and complemented by document analysis of regional land protection regulations. Productivity was recalculated using official harvested area and production statistics, and long-term projections to 2035 were constructed under annual land conversion scenarios of 1% and 2%. The results suggest that merely designating land is not enough to ensure sustainable food production over the long term. To maintain the resilience of regional food systems, governance must effectively incorporate measurable efforts to restore soil quality and control land conversion.